Do We Translate the Original Author’s Intended Meaning? - Frank, David B. (2016)
Translation of the Bible or any other text unavoidably involves a determination about its meaning. There have been different views of meaning from ancient times up to the present, and a particularly Enlightenment and Modernist view is that the meaning of a text amounts to whatever the original author of the text intended it to be. This article analyzes the authorial-intent view of meaning in comparison with other models of literary and legal interpretation. Texts are anchors to interpretation but are subject to individualized interpretations. It is texts that are translated, not intentions. The challenge to the translator is to negotiate the meaning of a text and try to choose the most salient and appropriate interpretation as a basis for bringing the text to a new audience through translation.
Keywords: authorial intent; Interpretation; originalism; Philosophical Hermeneutics; textual meaning